2020
DOI: 10.1158/1078-0432.ccr-20-1141
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Natural Killer Cell–Based Adoptive Immunotherapy for the Treatment of Patients with NSCLC after Radiochemotherapy: A Randomized Phase II Clinical Trial

Abstract: Purpose: Non-small cell lung cancer (NSCLC) is a fatal disease with poor prognosis. A membrane-bound form of Hsp70 (mHsp70) which is selectively expressed on high-risk tumors serves as a target for mHsp70-targeting natural killer (NK) cells. Patients with advanced mHsp70-positive NSCLC may therefore benefit from a therapeutic intervention involving mHsp70-targeting NK cells. The randomized phase II clinical trial (EudraCT2008-002130-30) explores tolerability and efficacy of ex vivo-activated NK cells in patien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 46 publications
0
36
0
Order By: Relevance
“…Herein, we have shown that high cytosolic levels of Hsp70 are associated with a more aggressive glioma type, but extracellular Hsp70 levels might act as a DAMP to stimulate NK cells. This hypothesis is supported by promising data of phase I and II clinical trials using ex vivo Hsp70 peptide and IL-2 stimulated NK cells to treat patients with advanced colon and lung cancers after radiochemotherapy [13,14]. The stimulation of patient-derived, anergic NK cells with Hsp70 peptide plus IL-2, but not with IL-2 alone, significantly enhanced the cytolytic activity of NK cells against membrane Hsp70+ tumor cells [13], and favorable clinical responses in a randomized phase II clinical trial could be attributed to an increased prevalence of activated CD94+ NK cells [14] that are responsible for the interaction with Hsp70 [31].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Herein, we have shown that high cytosolic levels of Hsp70 are associated with a more aggressive glioma type, but extracellular Hsp70 levels might act as a DAMP to stimulate NK cells. This hypothesis is supported by promising data of phase I and II clinical trials using ex vivo Hsp70 peptide and IL-2 stimulated NK cells to treat patients with advanced colon and lung cancers after radiochemotherapy [13,14]. The stimulation of patient-derived, anergic NK cells with Hsp70 peptide plus IL-2, but not with IL-2 alone, significantly enhanced the cytolytic activity of NK cells against membrane Hsp70+ tumor cells [13], and favorable clinical responses in a randomized phase II clinical trial could be attributed to an increased prevalence of activated CD94+ NK cells [14] that are responsible for the interaction with Hsp70 [31].…”
Section: Discussionmentioning
confidence: 85%
“…Due to the smaller size, favorable biodistribution, higher purity and easier GMP-production the Hsp70-peptide TKD is advantageous to recombinant Hsp70 protein for stimulating of NK cells. A pilot [12] and clinical phase I study [13] demonstrated excellent safety profiles of ex vivo TKD/IL-2-activated, autologous NK cells, and patients with advanced NSCLC showed promising clinical responses in a randomized clinical phase II trial after adoptive transfer of ex vivo TKD/IL-2-activated NK cells [14]. Apart from a study in grade IV glioblastoma/astrocytoma patients [15] insight into the expression and localization of Hsp70 in different types of brain tumors and its impact on the prevalence and activity of NK cells is limited.…”
Section: Introductionmentioning
confidence: 99%
“…HSP90 showed to affect CD3 and CD28, thus, the effect of HSP90 on CAR-containing CD3 and CD28-derived domains requires further investigation (133). From the other hand, HSP70-derived peptide TKD has been used for ex vivo activation of NK cells for adoptive transfer therapy and, since no severe toxicity was observed for NK-based immunotherapy, this strategy may be exploited for the development of lymphoma immunotherapy (140). In light of the reported, two research teams proposed to target membrane-bound HSP70 and HSP90 isoforms on tumors by CARs (134,136).…”
Section: Discussionmentioning
confidence: 99%
“…Chimeric Antigens Receptor (CAR) targeting CD19 and CD30 showed promising results in patients with r/r lymphoma (93,129,131,132). Autologous NK cells pre-activated with cytokines (IL-2, IL-15) and 14-mer HSP70-derived peptide (TKD) can be used for ex vivo activation of NK cells for the adoptive transfer therapy (137)(138)(139)(140). Anti-HSP70 and HSP90 CARs were proposed for specific targeting of membranebound forms of HSP70 and HSP90 (134,136).…”
Section: Hsps and Emerging Lymphoma Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation